Identifikasi Pengaruh Pola Perubahan Lahan Terhadap Zona Nilai Tanah Di Kecamatan Ungaran Barat Kabupaten Semarang - Bodro Sisvinta hayu; Andri Suprayogi; Hani'ah . . (Jurnal Geodesi UNDIP, 2014)
Districts of West Unggaran is a district located in Semarang regency . This sub-district is a district that holds a lot of potential biological and human potential , create a heterogeneous society ungaran district west into areas rich in culture . West ungaran also known as water catchment areas and the lungs of the city of Semarang . Because of its natural beauty , West Unggaran also often uses as an object of natural and cultural tourism development . Such condition can lead to changes in land use that have an impact on changes in the value of land .This research was originally conducted as mapping zone land value Unggaran District West with Data Processing Application software ArcView 3.3 BPN version for 2006 and 2010, the next step is making land use map changes price ArcGIS 9.3 software . In the final stage overlay between  with a map of changes in land with  zone map land value , to find changes of  the land value  for 2006 and 2010 .Research results indicates that  the span of 2006 to 2010 changes occurred in the largest land prices for residential zone Rp.4.230.000 , -. Where buildings / grounds changes  into the building / grounds in the Village Bandarjo , while the smallest price change happened zone agricultural land amounting to Rp 13,000 , - ie a change rainfed rainfed Branjang Village . it can be concluded there are differences in the average increase in the market value of the land . For the spread pattern of land prices can be concluded on the market price is higher than the residential zone by zone fields . Keywords : Change of land and land values .